Edukasi tentang Pelaksanaan Senam Hamil Trimester III di Desa Langa Kecamatan Syamtalira Bayu Kabupaten Aceh Utara - Elizar Elizar; Jasmiati Jasmiati; Hendrika W.K. Putri; Lisni Lisni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Pregnancy exercise is a fitness program for pregnant women. Therefore, pregnancy exercise has a special movement principle that is adapted to the condition of pregnant women. Pregnancy exercise is very important for pregnant women 22 weeks after pregnancy so that it can reduce the incidence of low birth weight and premature birth. The purpose of pregnancy exercise is to maintain the condition of the muscles and joints that play a role in the birth mechanism, improve physical health and self-confidence, and support childbirth and the mother's physiological response. The problem-solving method used is educating through presentations on pregnancy exercise, demonstrating and redemo- ting pregnancy exercise movements, and distributing pamphlets containing the physical activities of pregnant women and their benefits. At the time of conducting community service activities the participants who attended were 3rd trimester pregnant women, 1 Village Midwife, 1 cadre. The pretest value of the knowledge of the target audience before participating in the counseling activity was in the good category only 25% but after attending the counseling their knowledge increased to good, namely 87.5% and had good skills (75%) in doing pregnancy exercise. Participants were enthusiastic about the education delivered, none of the participants left the counseling center and took part in the pregnancy exercise red demonstration. This proves that the participants paid attention to the counseling and demonstration materials presented. Pregnancy exercise education is very important for mothers considering the benefits for pregnant women to improve health and well-being.